(untitled) (Research, Society and Development, 2022)
Anxiety may be associated with an increased risk of developing obesity, as it can cause changes in cortisol production in stressful situations. Objective: to identify sociodemographic and clinical aspects, BMI, and the association with the presence of comorbidity in patients with anxiety who underwent bariatric surgery. Method: cross-sectional study, survey type. We used an online questionnaire through the Google Forms platform assessing before and after surgery. Results: sample composed of 5,160 participants, divided into four groups: group A, 1,796 individuals who had no anxiety and did not develop anxiety after surgery; group B, 410 individuals who had anxiety and remained; group C, 1,391 who had anxiety and improved and group D with 1563 participants who had no anxiety and developed after surgery. The mean age was 37.25 years, female prevalence, married, from the southeastern region. In all groups there was a significant reduction in smoking, alcohol consumption and greater adherence to physical activity after surgery. The gastric bypass technique was the most prevalent. It was observed that group D developed anxiety after surgery and improvement in preexisting comorbidities. Dumping syndrome was more prevalent in groups B and D. Conclusion Bariatric surgery favors improvement in anxiety levels and preexisting comorbidities, however, it is possible that it is a risk factor for the emergence of anxiety in those who did not present it before the intervention.